2014
DOI: 10.1016/j.jval.2014.03.498
|View full text |Cite
|
Sign up to set email alerts
|

Reanalysis of Cost-Effectiveness of Abiraterone Acetate as Second Line Treatment for Metastatic Castration-Resistant Prostate Cancer in Japan Using a Japanese Claim Data Set

Abstract: Objectives: Italian recommendations for human papillomavirus (HPV) immunization currently consider females only. However, males can be vectors in viral transmission and at risk of infection. The BEST II study was designed to evaluate: the cost-effectiveness (CE) of different interventions targeting females as well as males; and the economic impact of vaccination on a wide range of HPV-induced diseases. MethOds: A dynamic Bayesian Markov model was developed to investigate the transmission between sexual partner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Although costs varied widely among the patients, our model estimated the mean health care costs to be ¥97,506 ($952) per patient per month. Our estimate was similar to that of a previous study (Shibahara et al 2014 ), which estimated costs to range from ¥53,090 (US$518) to ¥91,060 (US$889). In addition, our analysis showed that these costs were not strongly associated with death, but were significantly affected by variations in hospitalization and chemotherapies.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Although costs varied widely among the patients, our model estimated the mean health care costs to be ¥97,506 ($952) per patient per month. Our estimate was similar to that of a previous study (Shibahara et al 2014 ), which estimated costs to range from ¥53,090 (US$518) to ¥91,060 (US$889). In addition, our analysis showed that these costs were not strongly associated with death, but were significantly affected by variations in hospitalization and chemotherapies.…”
Section: Discussionsupporting
confidence: 89%
“…After proof of effectiveness was demonstrated, the cost-effectiveness of abiraterone was investigated. NICE estimated the ICER for abiraterone to be £46,800 (approximately US$50K)/QALY (Dyer et al 2012 ), Zhong et al estimated US$94K/QALY (Zhong et al 2013 ), Wilson et al estimated US$123.4K/QALY (Wilson et al 2014 ), and Shibahara et al estimated US$170K/QALY for Japanese patients (Shibahara et al 2014 ). Although a universally accepted threshold amount has yet to be determined, these estimates can be considered high when using an ICER threshold of US$50K/QALY (Neumann et al 2014 ), thereby indicating that abiraterone may not be cost-effective.…”
Section: Castration-resistant Prostate Cancermentioning
confidence: 99%
See 1 more Smart Citation